Ketergantungan Ekonomi Pada Sektor Migas : Diversifikasi Sebagai Upaya Mengurangi Risiko Ekonomi - Edy Soesanto; Citra Wahyuningrum; Ani Handayani (Lembaga Pengembangan Kinerja Dosen, 2024)
This research addresses the issue of economic dependence on the oil and gas sector and the efforts of economic diversification as a solution to reduce economic risks. We explain the benefits of economic diversification, such as economic stability and risk reduction, and provide case studies of countries that have succeeded in diversification. We also discuss the challenges and obstacles related to economic diversification, along with relevant policy recommendations. The findings highlight the importance of strategic measures in achieving more stable and sustainable economic growth.